Discourse Analysis and Document Analysis: SGML, Scholarly Publishing and Structuralist Theory - Campbell, D. Grant (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper studies the SGML Document-Type Definition for journal articles, created by Elsevier Science Publishers. Using the structuralist theory of Roland Barthes to analyze the various levels on which discourse is produced, the paper concludes that DTDs define many features of discursive structure by determining the hierarchy and grammar of elements and element sequences. . .